2018
DOI: 10.1089/thy.2018.0257
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Primary Hypothyroidism and Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis

Abstract: This large and updated meta-analysis shows that the presence of variably defined hypothyroidism is significantly associated with the presence and severity of NAFLD. However, the observational design of the eligible studies does not allow for proving causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 42 publications
1
89
0
6
Order By: Relevance
“…As free T4 levels drop, the risk of nonalcoholic fatty liver disease (NAFLD) increases across the spectrum of euthyroidism and hypothyroidism. (101) Conversely, NAFLD is associated with hypothyroidism. (102) TH, TH metabolites, TRβ agonists, and liver-specific analogs have been studied as potential therapeutics for treating both serum dyslipidemias and as a potential therapy for NAFLD.…”
Section: Th and Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…As free T4 levels drop, the risk of nonalcoholic fatty liver disease (NAFLD) increases across the spectrum of euthyroidism and hypothyroidism. (101) Conversely, NAFLD is associated with hypothyroidism. (102) TH, TH metabolites, TRβ agonists, and liver-specific analogs have been studied as potential therapeutics for treating both serum dyslipidemias and as a potential therapy for NAFLD.…”
Section: Th and Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Furthermore, key information errors were found in two review protocols, confusing the exposure and outcome subgroup leading to a lack of clarity [24,27]. Other errors were discovered including the fact that protocols did not provide the details of the search strategy, despite the fact that the published review [34] stated explicitly that the detailed search strategy could be found in the protocol.…”
Section: The Results Of Comparisonmentioning
confidence: 99%
“…Furthermore, key information error was found in one review protocol (confusing the exposure and outcome [24]). We believe it's also necessary to verify these changes, as well as investigate the reasons through correspondence with the authors.…”
Section: Implications For Future Researchmentioning
confidence: 99%